The science of feelings what psychological research tells us about our emotions - Tee, Eugene (Sunway shorts, 2021)
What are emotions and why do we experience them ? In the last 50 years or so, psychological science has shed light on the essence of what makes us human - why we experience a range of feelings from joy to sadness, anger to fear, and compassion to contempt. Yet, the science of emotion remains mostly inaccessible to the curious reader and those outside academic circles. This book is a story of our emotions ; a story of why and how we feel as human beings. It is a tale of our emotions, told by philosophers, biologist, neuroscientists, sociologists, and economists.Drawing on the rich psychological research on emotions, this book invites and understand how feeling states defines us and our humanity.